(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the role of modern technologies in ensuring high-quality organization of teaching and learning processes in contemporary education systems. It focuses on the pedagogical transformation driven by digital tools, interactive platforms, and smart learning environments. The study analyzes how technology-enhanced instruction improves learning outcomes, increases student engagement, and supports individualized learning pathways. Particular attention is given to the practical implementation of digital pedagogical strategies in higher education. The findings demonstrate that modern technologies significantly enhance instructional quality when integrated with well-structured methodological approaches and pedagogical design.